Durability of non-nucleotide reverse transcriptase inhibitor-based first-line ART regimens after 7 years of treatment in rural Uganda: A prospective cohort study. Issue 19 (14th May 2021) - Nanfuka, Mastula; Forrest, Jamie I.; Zhang, Wendy; Okoboi, Stephen; Birungi, Josephine; Kaleebu, Pontiano; Zhu, Julia; Tibenganas, Samuel; Moore, David M.
Abstract : Abstract: Most antiretroviral therapy (ART) programs in resource-limited settings have historically used non-nucleotide reverse transcriptase inhibitor (NNRTI)-based regimens with limited access to routine viral load (VL) testing. We examined the long-term success of these regimens in rural Uganda among participants with 1 measured suppressed VL. We conducted a prospective cohort study of participants who had been on NNRTI-based first-line regimens for ≥4 years and had a VL <1000 copies/mL at enrollment in Jinja, Uganda. We collected clinical and behavioral data every 6 months and measured VL again after 3 years. We quantified factors associated with virologic failure (VF) (VL ≥ 1000 copies/mL) using Wilcoxon Rank Sum, chi-square, and Fisher's Exact Tests. We enrolled 503 participants; 75.9% were female, the median age was 45 years, and the median duration of time on ART was 6.8 years (IQR = 6.0–7.6 years). Sixty-nine percent of participants were receiving nevirapine, lamivudine, and zidovudine regimens; 22.5% were receiving efavirenz, lamivudine, and zidovudine; and 8.6% were receiving other regimens. Of the 479 with complete follow-up data, 12 (2.5%) had VL ≥ 1000 copies/mL. VF was inversely associated with reporting never missing pills (41.7% of VFs vs 72.8% non-VFs, P  = .034). There were differences in distribution of the previous ART regimens ( P  = .005), but no clear associations with specific regimens. There was no association between having a VL of 50 to 999 copies/mL at enrollment and later VF ( P  = .160). Incidence of VF among individuals receiving ART for nearly 7 years was very low in the subsequent 3 years. NNRTI-based regimens appear to be very durable among those with good initial adherence.